(untitled) (Revista Científica Integrada, 2023)
Objective: to describe the characteristics of pregnant women infected with SARS-CoV-2 and newborns in São Lourenço Valley during the COVID-19 pandemic. Methods: Cross-sectional, epidemiological study, conducted from the notification records of pregnant women with COVID-19, in Vale de São Lourenço, state of Mato Grosso, between January 2020 and June 2022. Data collection was started via the notification system of infection by Sars-Cov-2 in Indica-SUS. Finding the outcome of the delivery and characterization of the binomial, through an individual search in the Information System on Live Births in the local base of each municipality. Results: In Indica-SUS, 28 positive pregnant women for COVID-19 were notified. The main symptoms recorded were cough, fever, and headache. Of these, 15 declarations of births were in the Information on Live Births. Most had more than six prenatal consultations and a gestational age of 37 weeks, until delivery. The prevalent type of delivery was cesarean section (86.66%). Of the newborns, only one was born with low weight, and all had an APGAR index of 7 to 10, in the 1st and 5th minutes. Conclusions: it was not possible to show significant harm inherent to infection by SARS-CoV-2, probably because it was a small number of patients, young and without comorbidities or other intercurrences during pregnancy.